Analisis Pelanggaran Kode Etik Anggota Kelompok Penyelenggara Pemungutan Suara dalam Pemilihan Gubernur Sumatera Barat 2020 di Tempat Pemungutan Suara 1 Desa Salak, Kota Sawahlunto - Sumarni Sumarni; Indah Adi Putri; Aidinil Zetra (Mahesa Research Center, 2023)
Abstract This research aims to describe the process of ethical code violations and analyze the factors causing ethical code violations by members of the Polling Organizers Group (KPPS) in the 2020 West Sumatra Governor Election at Polling Station (TPS) 1 in Salak Village, Talawi Sub-District, Sawahlunto City. This study uses a qualitative descriptive approach with a case study method. The theory used is election malpractice. The results of the study show that there were violations of the ethical code committed by KPPS members at TPS 1 in Salak Village due to the non-compliance of KPPS members in following the rules before the voting process. Violations occurred because KPPS members had not prepared the ballot tools in the voting booth. Voters were not well-informed about the correct voting procedures according to regulations. Factors causing ethical code violations by KPPS members at TPS 1 in Salak Village, Sawahlunto, include KPPS members' inability to work professionally, their limited understanding of the election regulations, insufficient supervision by Polling Station Supervisors (PTPS) during the voting process, lack of communication and coordination between KPPS officers and PTPS, Polling Station Committees (PPS), and Sub-District Election Committees (PPK), as well as inadequate quality of resources and training for KPPS.